Postgraduate students' use of information and communication technologies in educational research: a case study of International Centre for Educational Evaluation(ICCE), University of Ibadan (2005)
The whole world can be regarded as small village where information sharing is becoming less cumbersome. The postgraduate students should not be left behind in this recent technology of information and communication. However, not all the postgraduate students use these Information and Communication Technologies(ICTs) in their quest to obtain a higher degree. Therefore, this study examines the extent of the use of the ICTs among the postgraduate students of the International Centre for Educational Evaluation, University of Ibadan. The students used in the study were one hundred and forty one (141); sixty-seven (67) male and seventy-four (74) female. Forty-two (42) were in the in-service programme and thirteen (13) were in the regular programme, sixty-four (64) were in the PGDE (part-time) programme and twenty-two (22) were in the M.Phil/Ph.D programme. The results showed that not all the postgraduate students could get information from the internet and very few students made use of mobile phone to seek information on their research work. The implications of the study are discussed.